2015
DOI: 10.1055/s-0035-1556075
|View full text |Cite
|
Sign up to set email alerts
|

Ascending Aortic Proaneurysmal Genetic Mutations with Antiatherogenic Effects

Abstract: Thoracic aortic aneurysms are common and are associated with a high morbidity and mortality. Despite this lethal diagnosis, there is an increasing body of evidence to suggest that the diagnosis of an aneurysm, specifically in the ascending thoracic aorta, may significantly reduce the risk of developing systemic atherosclerosis. Clinical observations in the operating room have shown pristine blood vessels in patients undergoing surgery for thoracic aortic aneurysms. There is now evidence that both the carotid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…However, CVD are the leading cause of death in patients with DM and the risk of CVD in patients with DM is more than double that of patients without DM [ 9 ]. However, the relationship between diabetes and aortic dissection is still not completely clear [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, CVD are the leading cause of death in patients with DM and the risk of CVD in patients with DM is more than double that of patients without DM [ 9 ]. However, the relationship between diabetes and aortic dissection is still not completely clear [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may indicate that atherosclerosis plays a greater role in the pathogenesis of abdominal aortic aneurysm than in that of thoracic aortic aneurysm, as shown in previous studies. 27 , 28 , 29 A study comparing patients with ascending aortic aneurysm with controls showed less arterial calcification evaluated by computed tomography in the patients than in the controls. 27 Another study comparing the prevalence of coronary heart diseases and myocardial infarction in patients with a history of thoracic aortic aneurysm with that in controls identified a lower prevalence of coronary heart disease and myocardial infarction in the patients than in the controls.…”
Section: Discussionmentioning
confidence: 99%
“… 28 As for a biologic mechanism of thoracic aortic aneurysm, an excess proteolytic balance of matrix metalloproteinase activity, with transforming growth factor‐β modulating the extracellular matrix, is likely to lead to fragmentation of the elastic lamellae and disordered collagen deposition, which protects against plaque formation. 29 …”
Section: Discussionmentioning
confidence: 99%